2012
DOI: 10.1017/s0033291712002413
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that hippocampal–parahippocampal dysfunction is related to genetic risk for schizophrenia

Abstract: Our findings suggest that the pathophysiological mechanism underlying the inability of patients with schizophrenia to properly engage the H-PH during episodic memory is related to genetic risk for the disorder. Therefore, H-PH dysfunction can be assumed as a schizophrenia susceptibility-related phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 67 publications
2
21
0
Order By: Relevance
“…To our knowledge, so far, only 2 studies have explored hippocampal-parahippocampal abnormalities during declarative memory with fMRI in genetically high-risk populations. 24,25 Both found abnormal hippocampal-parahippocampal recruitment similar to our results, although the differences in clinical status, 24 sex, and performance 25 of the high-risk participants vs the comparison group of NCs left unresolved whether the observed deficit was due to familial/genetic background or was due to these other confounding factors. Our findings are also consistent with the results of 2 magnetic resonance spectroscopic imaging studies that found reduced Nacetylaspartate-an in vivo marker for neuronal synaptic abundance-in the hippocampus both in PTs and their SIBs 37,38 and with those from behavioral studies that reported deficient performance on declarative memory tests in unaffected relatives.…”
Section: Hippocampal-parahippocampal Function and Visual-memory Capacitysupporting
confidence: 84%
See 1 more Smart Citation
“…To our knowledge, so far, only 2 studies have explored hippocampal-parahippocampal abnormalities during declarative memory with fMRI in genetically high-risk populations. 24,25 Both found abnormal hippocampal-parahippocampal recruitment similar to our results, although the differences in clinical status, 24 sex, and performance 25 of the high-risk participants vs the comparison group of NCs left unresolved whether the observed deficit was due to familial/genetic background or was due to these other confounding factors. Our findings are also consistent with the results of 2 magnetic resonance spectroscopic imaging studies that found reduced Nacetylaspartate-an in vivo marker for neuronal synaptic abundance-in the hippocampus both in PTs and their SIBs 37,38 and with those from behavioral studies that reported deficient performance on declarative memory tests in unaffected relatives.…”
Section: Hippocampal-parahippocampal Function and Visual-memory Capacitysupporting
confidence: 84%
“…To our knowledge, so far, only 2 studies have reported impairment of HF recruitment in siblings of patients with schizophrenia during a declarative memory task. 24,25 However, it is uncertain whether the abnormality observed in these prior studies represents a pure trait phenomenon or is confounded by other state variables that could bias the results such as risk for conversion to psychosis 24 or poor memory performance 25 in these prior samples of siblings. It also is preferable to study siblings rather than parents because age is a state factor that affects memory and brain physiology.…”
mentioning
confidence: 99%
“…Together with the amygdala, the parahippocampal gyrus assumes an important role in emotional processing and goal-directed processes ( 52 ). Furthermore, a recent functional study also provided evidence that hippocampal-parahippocampal dysfunction is related to genetic risk of developing schizophrenia ( 53 ). Our meta-analysis, however, did not find a grossly decreased volume of the hippocampus, which is has been reported as a pronounced change in non-psychotic first-degree relatives of schizophrenia patients in previous studies using ROI analysis ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the consistently observed impaired memory performance in schizophrenia patients (Mesholam-Gately et al, 2009), previous neuroimaging studies in schizophrenia patients and at-risk populations repeatedly revealed decreased encoding-related activity in the hippocampal formation. In particular decreased parahippocampal activity during encoding of neutral visual and verbal stimuli has been associated with the strengths of memory impairments in schizophrenia patients as well as their first degree relatives and, thus, has been suggested to represent a potential intermediate biological phenotype related to an increased risk for schizophrenia (Rasetti et al, 2014, Thermenos et al, 2007Di Giorgio et al, 2013).…”
Section: Valence-unspecific Effects Of Ketaminementioning
confidence: 99%